2012
DOI: 10.5796/electrochemistry.80.315
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical Investigation on Permeability of Organic Acid Ions Through Amphotericin B Channels

Abstract: The influence of the channel-forming compound (amphotericin B) on the ion transport between two aqueous phases (W1 and W2) across the bilayer lipid membrane was electrochemically investigated. Sodium salts of organic acids (Na + Org − ) were used as electrolytes in W1 and W2. When the concentrations of Na + Org − in W1 and W2 are asymmetrically different, the permeabilites of Na + and Org − were estimated from the zero-current membrane potential. In the presence of amphotericin B, the permeability of Org − is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2013
2013
2013
2013

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 6 publications
(6 reference statements)
0
1
0
Order By: Relevance
“…Next, we recently confirmed that several organic acids with molecular sizes comparable to those of glucose, including gluconic acid, a two-electron oxidation product of glucose, permeated through the bilayer lipid membrane via the AmB channels. 13 The product that is smaller than the AmB channel is likely to flow out of the liposome; the lack of the product outside the liposome will drive diffusion of the product into the bulk solution. This outflow may contribute to stabilization of the current by minimizing reverse reactions; the enzymes and the cofactor remain in the capsule because they are not able to permeate the AmB channels.…”
mentioning
confidence: 99%
“…Next, we recently confirmed that several organic acids with molecular sizes comparable to those of glucose, including gluconic acid, a two-electron oxidation product of glucose, permeated through the bilayer lipid membrane via the AmB channels. 13 The product that is smaller than the AmB channel is likely to flow out of the liposome; the lack of the product outside the liposome will drive diffusion of the product into the bulk solution. This outflow may contribute to stabilization of the current by minimizing reverse reactions; the enzymes and the cofactor remain in the capsule because they are not able to permeate the AmB channels.…”
mentioning
confidence: 99%